Strengthening Character Education in Elementary School Students through Local Wisdom–Based Traditional Games - Yulia Sri Astuti; Sindi Apriliani (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Local wisdom refers to the environmental and cultural knowledge passed down through generations, which exists within community life. In education, integrating local wisdom can enhance character education by instilling moral values grounded in the local culture. Objective: This study aimed to explore the strategies employed by principals and teachers to enhance the character education of SDN Kawunggading students through locally wisdom-based games. Method: This research is qualitative in nature and employs a descriptive method. The study was conducted at SDN Kawunggading during the 2023 school year, with students as the subjects. Data were collected from the Principal and Homeroom Teacher using observation and interview techniques. The data analysis employed a descriptive analytical method. Results: The findings indicated that character education at Kawunggading Elementary School is implemented through local wisdom-based games, which help foster values such as honesty, tolerance, discipline, hard work, independence, responsibility, and friendliness (communicativeness). Conclusion: The integration of local wisdom-based games effectively supports the cultivation of character education, making it more relatable and meaningful for students. These games play a key role in promoting positive behaviors and values in students, while also preserving cultural heritage. Contribution: This study contributes to the understanding of how local wisdom-based methods can be effectively incorporated into character education in schools, offering practical insights into the use of cultural games to reinforce moral values among students.